How do medical teachers in Mauritius feel about teaching-learning communication skills? Development of a tool of communication skills teaching-learning perception score - Mutalik, Madhav; Mutalik, Maitreyee; Srivastava, Rama (International Journal of Research in Medical Sciences, 2017)
Background: Since communication skills (CS) are essential for medical professionals, many medical institutes have included communication skills as an integral part of medical curriculum. The present study was done to assess the perceptions of medical teachers in a medical college in Mauritius towards teaching and learning communication skills. Methods: A 14-item questionnaire with modified Likert-like scale was designed and administered to medical teachers at a medical college in Mauritius to assess their perceptions on teaching-learning communication skills. Positive scale scores and negative scale scores were calculated to know the perceptions on positive-sounding and negative-sounding items respectively. Based on these scores, the “Communication skills teaching-learning perception score” (CSTLPS) was calculated. Results: The medical teachers had an average positive scale score of 21.7 (Range 12-28). Their average negative scale score was 15.7 (Range 10-20). The average CSTLPS was 6.0652 with a range of minus 6 to 17. More than 80 percent teachers agreed on all the positive-sounding items, whereas 50 or more percentage of teachers disagreed on most of the negative-sounding items. Conclusions: The medical teachers in Mauritius had a positive attitude towards teaching-learning communication skills in medical college. Finding out CSTLPS can serve as a useful tool.